(3eSGFd eYOhOI ef EedGA GdTjN CHj Ydi Hf SjfGs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3gPg eSGFd eYOhOI ef EedGA GdTjN CHj Ydi Hf SjfG , bOS Gddg QhMg GdeSGFd GdChdi s
(3BNQgG (B:s
(3aCUWdM GdNhGU hCWdbhG daX GdNGUjI Ydi eG cGf ef bHdgG , agPG gh RHOI GdcdGe ai GdNGUjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B174 s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B(255(33)) s
Keywords: (3GdWHs